Adaptation of Co-Cr metal copings made on two termination lines and manufactured with two techniques. - Gutiérrez Chanjón, Enrique Manuel (2019)
The new digitized technologies have allowed to migrate from the technique of lost cast wax by centrifugation (CPC) to the subtractive manufacturing by CAD / CAM as the technique of soft-block milling (SMB). Objective: The purpose of this study was to compare the marginal and internal adaptations in metal Co-Cr copes on two termination lines: chamfer and bevel made by two techniques: CPC and SMB. Material and Methods: Two Co-Cr master models with chamfer and bevel termination were made, 4 study groups were formed and 13 copings were made per group. For the evaluation of the marginal and internal adaptations the replication method was used in silicone, then with a stereomicroscope the marginal and internal discrepancies were evaluated. Results: For the marginal discrepancy between the two techniques, only statistically significant diﬀerences were observed for the bevel termination (p <0.05) in points A1 and A2 and in the chamfer termination statistically significant diﬀerences were observed (p <0.05) in points A1 and F1. In the internal adaptation comparing both techniques in the bevel termination, statistically significant diﬀerences were obtained (p <0.05) in points E1, E2, D1, C2 y D2. And in the chamfer termination, the results showed statistically significant diﬀerences (p <0.05) in all the points. Conclusions: The copes that presented better marginal adaptation were those made by SMB with the chamfer termination line, in the bevel termination line it was not possible to conclude which of the two techniques is better in marginal adaptation. The ones that presented better internal adaptation in both lines of termination, in the axial zone were the copings made using the CPC technique and in the occlusal area the SMB had better internal adaptation.